Reflections on Being an Actor: Life and Career of a Unique Theater - dos Santos Cunha, Maria José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This work reflects on the actor’s art of acting and establishes connections with the career of actress Eunice Muñoz, who played a leading role in the development of Portuguese culture. It aims to be a tribute to her memory and make her known to those who have not had that opportunity. The research, collection of literature consistent with the topic addressed, and development of the work allowed concluding that the actress is worthy of being remembered by all those who worked with her, lived with her, and grew up in the art of the stage, and to be an inspiration/aspiration for the future generations of actors.